Ulysse et son double - Jean-Michel Ropars (Annali Online dell'Università di Ferrara. Sezione Lettere, 2018)
Odysseus’s dual personnality, both positive and negative, reflects the dual personnality of the god Hermes, the god in which opposite forces are united. So he faces recurrently «doubles» reproducing the dark face of his contradictory personnality, namely Thersites and Dolon in the Iliad, and Iros in the Odyssey (it is also the ground for the final fight against the Suitors) : he hits them, hurts them or possibly eliminates them (in Plautus’s Amphitryon, Hermes-Mercurius does the same with his double, Sosius, Amphitryon’s servant). It looks like a kind of self sacrifice, commited against himself ; hence the underlying comparison of Odysseus with a sacrified deer.